Dwarfism in ancient times: from worship to rejection - Grzesiak, Hanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The objective of this paper is to outline some aspects of dwarfism in the Antiquity. The author focuses in particular on Ancient Egypt where one of the most prominent of gods – Bes – suffered from dwarfism. It was believed that little people were somehow connected to other Egyptians gods, which is why they were treated with respect and dignity. Different attitude towards little people can be seen in Ancient Israel where they were excluded from the society, as disability at the time was considered as a punishment from God. The paper also covers Ancient Greece. Aristotle was the first scholar to describe dwarfism. He noted in particular the intelligence of the little people, which according to him was not developed particularly well, compared to the rest of the society.